Edukasi Pentingnya Pemeriksaan Kehamilan Untuk Mengetahui Tanda Bahaya Kehamilan - Linawati Novikasari; Rilyani Rilyani; Aryanti Wardiyah; Riska Wandini; Muhammad Syamsul Muarif; Maida Saputri; Muhammad Irgi; Hilda Meilinda Safitri; Ray Krisna Dhitya; Anggun Istawala; Rama Rajasa Ferlanda Alam; Rika Juana (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
The global maternal mortality rate is very high, with around 287,000 women dying during pregnancy or after giving birth in 2020. Nearly 95% of all maternal deaths. Pregnancy examination carries out a series of prenatal tests to screen early for possible complications or health complications during pregnancy that could endanger the safety of the mother and fetus. This complication can be prevented and treated if the mother immediately seeks help from professional medical personnel. The aim of this activity is to increase respondents' knowledge regarding the importance of carrying out ANC examinations to find out the danger signs of pregnancy. Socialization methods in the form of lectures and questions and answers are used in this activity. It was found that respondents were very enthusiastic about listening to the material presented by the presenters. The conclusion from this activity is that prenatal examinations are very important during pregnancy. ANC examinations were carried out 6 times during pregnancy, by carrying out community service activities regarding the importance of ANC examinations.